Political Clientelism in Rural Areas: Understanding the Impact on Regional Head Elections in Indonesia - Noak, Piers Andreas (Journal of Ecohumanism, 2024)
Political clientelism is a strategy often used by candidates or political parties to gain electoral support by offering goods, money, or services in exchange for votes. In the rural context, this patron-client relationship develops more strongly due to the high economic and social dependency between communities and political actors. This research focuses on the phenomenon of political clientelism in rural areas and its impact on regional head elections in Indonesia. This research uses a qualitative approach with a descriptive approach. Research findings show that political clientelism in rural Indonesia, especially in agrarian areas, strengthens patron-client relationships in which political elites exploit the economic dependence of communities to gain support through material promises. This causes voters to vote based on short-term favors rather than the quality of the candidate, thereby exacerbating transactional politics and undermining the integrity of the election. Factors such as low political education, limited access to information, and economic instability reinforce citizens’ dependence on local patrons, including village heads, who have access to favors. As a result, the democratic process in rural areas is distorted, focusing more on the distribution of resources than on the vision of candidates, making systemic change difficult to achieve .